The effects of internal and external imagery, and badminton skills execution on muse measure among novice university badminton players - Chyi, Chua Chia (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
This study aimed to differentiate the brain wave activity between internal imagery and external imagery of badminton shots, and execution of badminton shots. A total of 8 participants (N = 8) were recruited in this study. They were randomly assigned into two groups: a) internal imagery group (n = 4) and b) external imagery group (n = 4), in which all of the participants performed the badminton skills execution. All participants obtained moderate to high scores in the Sport Imagery Ability Measure SIAM) and are in good health as measured by the Physical Activity Readiness Questionnaire. Participants wore the Muse headband while performing the badminton shots and while performing imagery of the badminton shots. The brainwaves activity was recorded and analysed. Results showed that internal imagery induced the highest delta wave, whereas the execution of badminton shots induced the highest theta, alpha, beta and gamma waves. However, the result was not statistically significant due to the small sample size.